1935
DOI: 10.1002/hlca.19350180176
|View full text |Cite
|
Sign up to set email alerts
|

Sur l'élasticité du caoutchouc

Abstract: 69. Sur 1'6lasticite du caoutchouc pax Kurt H. Meyer et Cesare Ferri. (25. 111. 35.)Pour expliquer l'~lasticit6 du caoutchouc, plubieurs auteurs supposent que les longues molecules en chaines ont tenclance ii s'enrouler en spirale et que, lorsqu'une force exterieure les Pcarte cle cette position d'hquilihre, elles cherchent a p retourner. Ces notions se laissent dkvelopper dans les cleux directions suivantes : 1 0 On peut admettre qn'entre les diverses parties tl'une m@me molPcule, par exemple entre les double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(49 citation statements)
references
References 2 publications
5
42
2
Order By: Relevance
“…This phenomenon is related with the so-called Gough-Joule effect, consisting in the length decrease of a rubber band extended by a suspended weight when it is heated. Following the first enunciation by Meyer and Ferri [38], it is currently assumed that the elastic behavior of rubber does not arise from the forces between molecules, but from the thermal energy of the atoms making up the long-chain molecules. The idea is widely accepted that its deformation involves reduction of entropy rather than an increase of internal energy, as occurs in "ordinary" solids [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is related with the so-called Gough-Joule effect, consisting in the length decrease of a rubber band extended by a suspended weight when it is heated. Following the first enunciation by Meyer and Ferri [38], it is currently assumed that the elastic behavior of rubber does not arise from the forces between molecules, but from the thermal energy of the atoms making up the long-chain molecules. The idea is widely accepted that its deformation involves reduction of entropy rather than an increase of internal energy, as occurs in "ordinary" solids [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…When # is independent of temperature, then (2.9) reduces to the power-law neo-Hookean model studied by Knowles [42], Tao and Rajagopal [37], and Zhang and Rajagopal [39].…”
Section: Static Solutionsmentioning
confidence: 99%
“…Knowles [42]) which can shear soften or shear stiffen, depending on the power-law exponent, by virtue of the shear modulus being dependent on the stretch tensor B. Knowles [42] showed that the equations of equilibrium for plane strain lose ellipticity when the power-law exponent n < 1/2. It is well known that material properties of rubber change significantly due to changes in temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the basic concept of macromolecular networks and entropic elasticity [18] were expressed more then 50 years ago, work on the physics of rubber elasticity [8,19,20,21] is still active. Moreover, the molecular theories of rubber elasticity are advancing to give increasingly realistic models for polymer networks [7,22].…”
Section: Rubber Elasticitymentioning
confidence: 99%